Enhancing the gamma radiation shielding performance: The impact of Bi2O3 and MgO nanoparticles on PMMA - Almutery, Aml; Rahman, Wan Nordiana; Mohamed, Faizal; Chia, Chin Hua; Abdul Razak, Khairunisak; Ab ashid, Raizulnasuha; Rilwan, U.; Sayyed, M. I.; Maghrbi, Yasser (Elsevier, 2025)
This work investigated the gamma radiation shielding performance of different nano-composites (pure PMMA, PMMA doped with Bi2O3, PMMA doped with MgO, and PMMA doped with Bi2O3–MgO) using the solution casting method. The experimental linear attenuation coefficients (LACs) of the samples were determined using a sodium iodide (NaI) detector and the results were compared with Phy-X theoretical results, where better matching was observed. At 59.5 keV, the PMMA doped with Bi2O3 sample had the largest LAC of 0.759 cm−1 when compared to the PMMA doped with Bi2O3–MgO sample with a LAC of 0.695 cm−1. At the same energy (59.5 keV), the radiation protection efficiency of the PMMA doped with Bi2O3 sample was 31.34 %, which was far greater compared to that of the PMMA doped with Bi2O3–MgO sample, thus confirming the PMMA doped with Bi2O3 sample as the optimum candidate to be applied for protection against gamma radiation.